ANALISIS KOMPETENSI SUMBER DAYA MANUSIA, TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN SKPD DI LINGKUNGAN PEMERINTAH KOTA METRO - Nelawat, Emi i; Suharto, Suharto; Mazni, Afdal (SIMPLEX: Journal of Economic Management, 2023)
The purpose of this study was to empirically examine the effect of competence of HR, information technology and internal control systems on the quality of SKPD financial reports. Respondents in this study were 54 people consisting of officials from the head of the finance sub section and staff who were directly involved in the preparation of financial reports at SKPD in Metro City. Based on the analysis results obtained from 54 samples regarding the influence of HR competence, information technology and internal control systems on the quality of financial reports, it can be concluded that the F test results indicate that all three have an effect on the quality of financial reports. This can be seen from the table of F test results with the calculation that 30,004 > Ftabel 2,79. And the Sig value is 0,000 < 0,05 and. Human resource competencies, information technology and internal control systems have a positive and significant impact on the quality of financial reports. The results of a simple regression test that were processed using the SPSS version 16.0 program obtained an equation, namely: Y = 13,675 + 0,411 X1 + 0,317 X2. + 0,226 X3 + et. From these equations, it can be seen that the three variables (X1, X2, X3) studied have a positive affect the variable quality of financial statements (Y). From this analysis it can be concluded that the competence of human resources, information technology and internal control systems have a direct effect on the quality of SKPD's financial reports.